Bacteremia caused by Anaerococcus SPP: Is this an underdiagnosed infection?. (August 2021) - Cobo, Fernando; Pérez-Carrasco, Virginia; González, Adrián; Sánchez-Martin, Victoria; García-Salcedo, José Antonio; Navarro-Marí, José María
Abstract: The objectives of this study were to report 10 episodes of clinically significant bacteremia caused by species of the genus Anaerococcus isolated between July 2018 and February 2021 from the microbiology laboratory of a tertiary hospital in Granada (Spain). None of the isolates were identified by MALDI-TOF MS, and the definitive species identification was performed by 16 S rRNA gene sequencing. No reference spectra of the Anaerococcus species were present in the MALDI-TOF MS database. Eight isolates were finally identified as A. octavius, one isolate as A. tetradius and the other as A. urinomassiliensis . The majority of these infections were seen in patients aged >70 years. Risk factors for anaerobic infection were observed in eight patients, especially diabetes mellitus, surgery, and the presence of cancer. Fever was present in all patients. Three patients died, but only one death was attributed to the infection. Mean detection time of positive blood cultures was 47.5 h (range 24–92 h). Antimicrobial susceptibility to penicillin, amoxicillin-clavulanate, imipenem, moxifloxacin, clindamycin, metronidazole, and piperacillin-tazobactam was tested using the gradient diffusion technique and EUCAST breakpoints (except for moxifloxacin). No resistance to amoxicillin-clavulanate, metronidazole, imipenem, or piperacillin-tazobactam was detected; however, the majority of isolates were resistant to clindamycin. When MALDI-TOF MS does not provide a correct identification at genus or species level, as in some isolates of Gram-positive anaerobic cocci, microbiologists should perform an additional confirmatory technique, such as gene sequencing analysis, to obtain a definitive diagnosis. Highlights: MALDI-TOF MS could not correctly identify some Anaerococcus species. Molecular techniques can help to achieve a definitive identification of Anaerococcus. Bacteremia due to Anaerococcus spp is mostly seen in older patients. Overall, antimicrobial resistance rates are low for this genus.